CARSHARING AND MOBILITY: A TURNING POINT FOR AUTOMAKERS AND SOCIETY - Furtado, Anderson Elias; Pascoal, Erik Telles; Ferreira Filho, Valter Silva (Revista Mackenzie de Engenharia e Computação, 2019)
Carsharing is already a reality in developed countries like USA, France, Germany and Japan. Nevertheless, several studies have been conducted by automakers and technology companies in these countries in order to improve business profitability. According to the projections of consultants and industry experts, the carsharing potential market for the next few decades is very positive, mainly encouraged by the growing environmental appeals and urban mobility. In this context, the objective of this paper is to present an overview of the main initiatives of the governments and automakers to develop this new market, whitin a zoom in Brazilian situation. At the end of this study it has been possible to identify the main difficulties and facilities, so as a path in Brazil in order to make a reality the use sharing vehicles in drivers’ daily lives.